IMPLEMENTASI MEMBRANE HOLLOW FIBER UNTUK MENINGKATKAN KUALITAS VCO PADA PENGERAJIN VCO - SUGITA, I.K.G.; Astawa, K.; Sri Komaladewi, A.A.I.A.; Priambadi, I.G.N. (Buletin Udayana Mengabdi; Vol 22 No 4 (2023): Buletin Udayana Mengabdi, 2023)
Virgin coconut oil (VCO) is one of the processed coconut oil products. The manufacturing process, especially the filtering process, uses a very simple system. The coconut milk filtering process uses by tissue paper that it arranged in layers. Tissue filtering certainly has a weakness because tissue is produced by a chemical process. This is very possible chemical particles will dissolve in the VCO during the filtering process. The tissue that used also does not have standardization on health. The "membrane hollow fiber" tool is designed as one way to reduce tissue deprivation as a vco filter. The object of this service was the craftsmen of VCO in the Selumbung village The implementation of VCO filtering is using a "hollow fiber membrane" which has a very good filter quality. The test results in the Analytical laboratory Udayana University, showed that there was a decrease in the water content in the VCO by 11%. The filtering process speed is 10 times faster than the manual system filtering speed. Keywords: Virgin coconut oil, productivity, membrane hollow fiber